Emergency veno-arterial extracorporeal membrane oxygenation (VA ECMO)-supported percutaneous interventions in refractory cardiac arrest and profound cardiogenic shock. (March 2021) - Radsel, Peter; Goslar, Tomaz; Bunc, Matjaz; Ksela, Jus; Gorjup, Vojka; Noc, Marko
Abstract: Aims: We investigated the spectrum of emergency veno-arterial extracorporeal membrane oxygenation (VA ECMO)-supported interventions including percutaneous coronary intervention (PCI), transcatheter aortic valve implantation (TAVI) and invasive electrophysiology (EP). Methods and results: Between June 2010 and February 2020, 52 consecutive patients underwent VA ECMO implantation for refractory cardiac arrest (E-CPR) and 78 for profound cardiogenic shock. Percutaneous interventions on VA ECMO included PCI (n = 29), TAVI (n = 4) and EP (n = 1). Surgical interventions were cardiac (n = 36) or non-cardiac (n = 5). During PCI, ECMO flow was maintained at 2.7 ± 1.0 L/min. Of the 40 treated lesions, 48% were located on left anterior descending and 20% on the left main artery. An average 2.0 ± 1.8 DES/patient with diameter 3.2 ± 0.5 mm and stented length 41 ± 35 mm were implanted. PCI success was 83%. TAVI was performed in 4 patients with left ventricular ejection fraction 21 ± 10% and mean aortic valve gradient 41 ± 5 mmHg. After successful valve implantation supported by 1.4 ± 0.1 L/min ECMO flow, mean gradient decreased to 11 ± 5 mmHg without significant aortic regurgitation. In one patient radiofrequency ablation of His bundle followed by permanent pacemaker implantation was performed under ECMO flow of 2.8 L/min. Overall survival to hospital discharge with good neurological recovery was 29% in E-CPR and 44% in profound cardiogenic shock. Conclusions: Our study showed feasibility and effectiveness of VA ECMO-supported percutaneous interventions in patients with profound hemodynamic collapse.